A review of the literature analyzing benefits and concerns of infliximab biosimilar CT-P13 for the treatment of rheumatologic diseases: focus on interchangeability - Becciolini A; Raimondo MG; Crotti C; Agape E; Biggioggero M; Favalli EG (Dove Medical Press, 2017)
Andrea Becciolini,1 Maria Gabriella Raimondo,2 Chiara Crotti,2 Elena Agape,2 Martina Biggioggero,2 Ennio Giulio Favalli1 1Department of Rheumatology, 2Department of Clinical Sciences and Health Community, University of Milan, Division of Rheumatology, Gaetano Pini Institute, Milan, Italy Abstract: The introduction of biological agents drastically changed the treatment paradigm of inflammatory arthritides, ameliorating the natural history of the diseases but concomitantly increasing the drug costs due to the manufacturing process. On this concern, biosimilar drugs may represent a valid option for reducing this elevated cost and increasing the availability of these highly effective treatments. Recently, CT-P13, the first biosimilar of infliximab, has been approved with the same indications established for the reference product (RP), and its daily use is progressively increasing. However, the experience with biosimilar drugs in the field of rheumatology is still limited, raising potential doubts and concerns on their correct management in real-life settings. Comparability analysis between CT-P13 and its RP was evaluated in equivalence randomized controlled trials (RCTs) – PLANETRA and PLANETAS – performed on patients with rheumatoid arthritis and axial spondylitis, respectively. CT-P13 and RP showed similar profile in terms of quality, biological activity, safety, immunogenicity, and efficacy. However, the interchangeability between infliximab RP and its biosimilar still represents the most challenging issue because of a lack of a long-lasting experience. To date, reassuring preliminary data on this topic were reported in open-label extensions of PLANETRA and PLANETAS RCTs and in ongoing real-life observational studies. These findings, taken all together, significantly affect the landscape of biosimilar regulatory pathways and strongly support CT-P13 introduction as a great opportunity for expanding the accessibility to these very effective and high-cost therapies. Keywords: biological therapy, biosimilars, interchangeability, TNF inhibitors, rheumatic diseases